‘Julle noem My Leermeester … en julle is reg, want Ek is dit’ (Joh 13:13). Onderrig in die Evangelie van Johannes - Van der Watt, Jan (Stellenbosch Theological Journal, 2016)
Teaching in John’s Gospel In this article the significance is analysed of the Johannine concept of teaching and related themes, like teachers, different ways of teaching, both formal and informal. Both terminological as well as conceptual references to teaching are considered. It is shown that the teaching of Jesus to his followers is described in terms of Jewish rabbinic activities and that social conventions in this respect are honoured. However, when the Father teaches Jesus, the metaphor changes to typical Jewish teaching within a family context where the father teaches his child through example. The child observes what the father says and mimes these actions and words. This ensures that the teaching of Jesus corresponds to that of the Father. When Jesus goes back to his Father, the Paraclete continues this educational process by reminding and guiding the followers of the words of Jesus. The Gospel however refrains from describing the followers of Jesus as teachers, but calls them witnesses to the teaching of Jesus – the teaching remains that of Jesus. This concept is so central to the theology of John that the theological structure would collapse if it would be ignored or downplayed.